Input-output analysis foundations and extensions - Miller, Ronald E. 1933-; Blair, Peter D. 1951- (Cambridge University Press, 2022)
"We started working on the first edition of this book (Miller and Blair, 1985) in the late 1970s. At that time, input-output as an academic topic (outside of Wassily Leontief's Harvard research group) was a little more than 25 years old - approximately 1952-1979. We use 1952 because that was when the first author was introduced to input-output analysis in a sophomore-year economics class at Harvard taught by Robert Kuenne, who later claimed that was the first time input-output had been included (anywhere) in an undergraduate economics course. In 1962, the first author joined the faculty of the Regional Science Department at the University of Pennsylvania. He was asked by then department chair Walter Isard to teach the graduate course in linear models for regional analysis; this was to include a strong input-output component. At that time coverage of the topic in texts was to be found primarily in two chapters of Dorfman, Samuelson and Solow (1958), in Chenery and Clark (1959), in Stone (1961) and in a long chapter on input-output at the regional level in Isard et al. (1960); later there were texts by Miernyk (1965), Yan (1969), and Richardson (1972).